2019
DOI: 10.1371/journal.ppat.1007675
|View full text |Cite
|
Sign up to set email alerts
|

Cell–cell fusion induced by reovirus FAST proteins enhances replication and pathogenicity of non-enveloped dsRNA viruses

Abstract: Fusogenic reoviruses encode fusion-associated small transmembrane (FAST) protein, which induces cell–cell fusion. FAST protein is the only known fusogenic protein in non-enveloped viruses, and its role in virus replication is not yet known. We generated replication-competent, FAST protein-deficient pteropine orthoreovirus and demonstrated that FAST protein was not essential for viral replication, but enhanced viral replication in the early phase of infection. Addition of recombinant FAST protein enhanced repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 52 publications
4
37
0
Order By: Relevance
“…Our results are consistent with those from other published studies showing that FAST proteins can enhance replication of dsRNA viruses on sub-single-cycle and multi-cycle time scales (32, 33). In one study, the authors detected enhancement of viral RNA synthesis in the presence of FAST proteins as early as five hours post infection, and they hypothesized that cell-to-cell fusion provides access to additional substrates for viral transcription, such as nucleotide triphosphates and S-adenosyl methionine (33). Since replication enhancement conferred by FAST proteins was detected even at high MOI, the authors suggested that enhancement is not mediated by cell-to-cell spread.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with those from other published studies showing that FAST proteins can enhance replication of dsRNA viruses on sub-single-cycle and multi-cycle time scales (32, 33). In one study, the authors detected enhancement of viral RNA synthesis in the presence of FAST proteins as early as five hours post infection, and they hypothesized that cell-to-cell fusion provides access to additional substrates for viral transcription, such as nucleotide triphosphates and S-adenosyl methionine (33). Since replication enhancement conferred by FAST proteins was detected even at high MOI, the authors suggested that enhancement is not mediated by cell-to-cell spread.…”
Section: Discussionsupporting
confidence: 93%
“…In numerous studies of RVB in pigs and cows, researchers have failed to note detection of syncytia, though they may not have been looking for such events. However, in a rodent model of infection with a fusogenic pteropine orthoreovirus (PRV), authors failed to detect syncytia in infected lung tissue when specifically looking for these cells (33). In the case of RVB infection, it has been suggested that syncytia are rapidly sloughed from the intestinal epithelium and therefore easily missed (51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the p14/p22 chimera reported here is substantially more potent than wild-type p14 or p22. This suggests that the fusogenicity of FAST proteins that perhaps selective pressures limit the potency of FAST protein fusion during viral infection in an organism (4). Although the actin cytoskeleton has yet to be implicated in other FAST proteins, similar chimeric fusogens with p10 from avian reovirus and p15 from baboon reovirus have also been shown to be functional (2,27), further supporting the idea that FAST family fusogen domains are modular.…”
Section: Discussionmentioning
confidence: 84%
“…Aquareovirus and orthoreovirus are two genera of the Reoviridae family of segmented doublestranded RNA viruses that form multinucleated syncytium after infection that increases viral spread and pathogenicity (1)(2)(3)(4). To drive cell-cell fusion, both aquareovirus and orthoreovirus express a non-structural, fusion-associated small transmembrane (FAST) protein on the plasma membrane of infected cells.…”
Section: Introductionmentioning
confidence: 99%